Tổng quan các khung lí thuyết để nghiên cứu về phát triển chuyên môn của giáo viên tiếng Anh - Trần, Hữu Nghị; Ngô, Huỳnh Hồng Nga; Trịnh, Quốc Lập (Tạp chí Giáo dục, 2025)
In today’s educational context, teachers’ professional development has become a key factor in responding to rapid changes in curriculum, pedagogy and educational technology. Particularly in the field of English language teaching - a global and ever-changing field, teachers need to enhance their knowledge and skills to improve the teaching quality and meet the diverse needs of learners. This paper introduces four theoretical frameworks commonly used in the field of English language teaching to study teachers' professional development, including Historical-Cultural Activity Theory, Ecological Systems Theory, Contextual Learning Theory, and Community of Practice Theory. Specifically, this paper examines the basic principles and practical applications of these theoretical frameworks, explaining in detail how they can be effectively applied to study and improve teachers' professional development. This study provides a theoretical foundation for future research on teachers' professional development in the field of English language teaching.